Was related mother´s depression and anxiety with drug consump-tion of your adolescents sons? - Becoña, Elisardo; López, Ana; Míguez, Mª Carmen; Lorenzo, Mª Carmen; Fernández del Río, Elena (Anales de Psicología / Annals of Psychology, 2009)
The family can act as a risk or protective factor in the behavior problems that appear during the adolescence, as the consumption of drugs. The objective of the present study is to analyze if there is relation-ship between the presence of depression and trait anxiety problems in mothers, and the consumption of drugs (tobacco, alcohol, cannabis and cocaine) in their sons. The sample is formed by 594 persons, 297 mothers and 297 sons selected at random, stratified by sex and age, of the area of Salnés (Pontevedra). The results indicate that the mothers whose sons have consumed cannabis and/or cocaine at some time, and that they have smoked tobacco in the last 6 months, they have more depressive symp-toms. It is also more probable than they have consumed alcohol (spirits) lifetime and in the last 6 months, and that they have drunkness, the sons of mothers that have a score above the normal population of reference.